CARACTERIZACIÓN DEL ESTILO HUALLA INCISO PUNZONADO DEL YCHSMA TEMPRANO - Dolorier, Camilo (2017)
This study discusses the entries are made in the archaeological literature about the presence of a decorated material on the basis of incisions and points. For it is analyzed, it classified and characterized a small collection of ceramic fragments from Huallamarca. This material is inserted into a larger collection showing stylistic, chronological and cultural coherence. This allowed us to identify recurrences and particularities and define its chronological position. So Hualla paragraph punching style, is assigned to the first part of the Late Intermediate Period (PIT 1-3). It also presents a particularity of the cultural component of this society, reflected in a kind of opposition and complements its cultural manifestations.